Public spending and economic growth in Zambia - an econometric analysis - Muyaba, Andrew Munsaka (Research of GSB, 2018)
The importance of understanding the relationship between fiscal policies and economic growth has inspired many scholars to investigate the underlying relationship between these variables. In Zambia the growth in public expenditure has become a topical issue in the light of escalating debt levels and widening budget deficit; as a result, the government is constantly under pressure to borrow to cover the deficit. The aim of this study was to analyze the effect of government expenditure on economic growth in Zambia. The study used secondary data which was sourced from the Zambian Ministry of Finance and World Bank websites for the period from 1991 to 2015. The data was analyzed using E-Views 9.5 student version. The econometric tools used to analyze the data are the Autoregressive Distribution Lag (ARDL) and the Pairwise Granger Causality Test. The variables included in the research are public expenditure and economic growth. Both variables were stationary at first difference. Empirical finding from the study indicates that there is a positive and significant relationship between public expenditure and economic growth in Zambia both in the short-run and the long-run. Further, Granger causality test demonstrated a unidirectional causality from public expenditure to economic growth. This finding validated the fact that the Zambian fiscal environment is aligned to the Keynesian theory as opposed to Wagner's Law. In essence, the study recommended more allocation of resources towards public expenditure, including exploiting public-private partnerships as a way of increasing expenditure towards social sectors and infrastructure without necessarily increasing the strain on government resources.